Efektivitas Penggunaan Media Pembelajaran Tiga Misi Rahasia Mencari Ide Pokok Kelas III Sekolah Dasar - Ulandari, Arum; Agustina, Dwi Kameluh; Rosyida, Desy Anindia (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Based on the results of the preliminary study conducted by the researcher, it shows that students have difficulty spelling the main idea questions, which on average in the initial score of class III A obtained a score of 29.6 while in class III B it was 26.6. This is because students' interest in reading is less and students' ability to understand reading texts. With these findings, the researcher hopes that using the learning media Three Secret Missions of Finding Main Ideas can make it easier for students to understand the main ideas. The research method was carried out using quantitative research with a quasi-experimental type of design in the form of pretest-postest control design group. The approach taken by the researcher aims to determine the effectiveness of using the learning media of the Three Secret Missions of Finding Main Ideas in the main idea material in elementary schools. The research procedure is carried out through three stages, namely (1) Preparation stage, (2) Implementation stage, (3) Reporting stage. The instruments used by the researcher include, observation, interviews, questionnaires (questionnaires), pretest-posttest questions, and documentation. Based on the results of research and data processing, an increase in value of 23.85% was obtained in the experimental class where the value increased from an average score of 29.65 to 53.5. The increase in scores that occurred in the experimental class showed that the media succeeded in improving students' understanding but was still not effective because it had not reached the Minimum Achievement Criteria score.